Is Vibrio fluvialis Emerging As a Pathogen with Epidemic Potential in Coastal Region of Eastern India Following Cyclone Aila? (Journal of Health, Population and Nutrition, 2010)
An isolated area with diarrhoea epidemic was explored at Pakhirala village of the Sundarbans, a coastalregion of South 24 Parganas district of West Bengal, eastern India. The Pakhirala village was surrounded byother villages affected by a similar epidemic. The affected villages experienced this epidemic following thecyclone Aila, which had hit the coastal region of the Sundarbans in eastern India. In Pakhirala, the situationwas the worst. Within a span of six weeks (5 June–20 July 2009), 3,529 (91.2%) of 3,871 residents wereaffected by watery diarrhoea. Of all the cases (n=3,529), 918 (26%) were affected by moderate to severediarrhoea. In other villages, 28,550 (70%) of the 40,786 people were affected; of them, 3,997 (14%) hadmoderate to severe watery diarrhoea. The attack rate and the severity of the cases were significantly higherin Pakhirala village compared to other affected villages. The laboratory results revealed that Vibrio fluvialiswas the predominant pathogen in Pakhirala village (5 of 6 laboratory-confirmed organisms) whereas Vibriocholerae O1 Ogawa was the predominant pathogen in other villages of Gosaba block (7 of 9 bacteriologically-confirmed organisms). This result indicates that V. fluvialis behaves more aggressively than V. choleraeO1 in an epidemic situation with a higher attack rate and a different clinical picture. An in-depth study isrequired to explore its pathogenicity in detail, geographical distribution, and possible control measures,including development of specific vaccine preparation and determination of its efficacy.Key words: Diarrhoea; Cyclone; Disasters, Natural; Vibrio cholerae; Vibrio fluvialis; IndiaDOI: 10.3329/jhpn.v28i4.6037J HEALTH POPUL NUTR 2010 Aug 28(4):311-317